Mediation of Organisational Commitment Empirical Study of Transformational Leadership, Job Satisfaction, and Perceived Organisational Support on Turnover Intention - Syaechurodji, Syaechurodji; Haryadi, Didit; Kania, Dewi; Darmawan, Dadan; Sanasa, Yoke (Universitas Mercu Buana, 2024)
Objectives: The phenomenon of turnover intention should be a concern for the company or organization owners. The phenomenon of turnover intention can be detrimental to the organization's survival. This study examines how the role of transformational leadership, job satisfaction, and perceived organizational influence turnover intention and how these roles modify organizational commitment.Methodology: This research uses quantitative research with a causality approach, with the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method. The reason is that PLS-SEM can predict complex latent variables from a study. This research was conducted on J & T Cargo expedition employees in Tangerang Regency and a total sample of 131, testing the inner model and outer model and bootstrapping tests to test the mediation of organizational commitment.Finding: As formulated in the hypotheses, the results are consistent, where transformational leadership and employee job satisfaction significantly affect turnover intention, but perceived organizational support has no significant impact on turnover intention. Similarly, transformational leadership, job satisfaction, and perceived organizational support significantly impact organizational commitment. Thus, organizational commitment mediates the significant effect of transformational leadership, job satisfaction, and perceived organizational support on turnover intention. Theoretical and practical implications are presented.Conclusion: Organizations that emphasize developing transformational leadership qualities and prioritizing employee satisfaction will be better positioned to avoid turnover intention. By recognizing and acting on these insights, organizations can build positive employee engagement, retention, and success cycles. In summary, transformational leadership and job satisfaction significantly affect turnover intention, as satisfied employees are less likely to consider leaving their current organization.